CYP2D6 Genotype and Adjuvant Tamoxifen: Meta‐Analysis of Heterogeneous Study Populations. Issue 2 (23rd September 2013) - Province, M A; Goetz, M P; Brauch, H; Flockhart, D A; Hebert, J M; Whaley, R; Suman, V J; Schroth, W; Winter, S; Zembutsu, H; Mushiroda, T; Newman, W G; et al.
<x xml:space="preserve">Abstract</x> The International Tamoxifen Pharmacogenomics Consortium was established to address the controversy regarding cytochrome P450 2D6 (CYP2D6) status and clinical outcomes in tamoxifen therapy. We performed a meta‐analysis on data from 4, 973 tamoxifen‐treated patients (12 globally distributed sites). Using strict eligibility requirements (postmenopausal women with estrogen receptor–positive breast cancer, receiving 20 mg/day tamoxifen for 5 years, criterion 1); CYP2D6 poor metabolizer status was associated with poorer invasive disease–free survival (IDFS: hazard ratio = 1.25; 95% confidence interval = 1.06, 1.47; P = 0.009). However, CYP2D6 status was not statistically significant when tamoxifen duration, menopausal status, and annual follow‐up were not specified (criterion 2, n = 2, 443; P = 0.25) or when no exclusions were applied (criterion 3, n = 4, 935; P = 0.38). Although CYP2D6 is a strong predictor of IDFS using strict inclusion criteria, because the results are not robust to inclusion criteria (these were not defined a priori), prospective studies are necessary to fully establish the value of CYP2D6 genotyping in tamoxifen therapy. Clinical Pharmacology & Therapeutics (2014); 95 2, 216–227. doi:10.1038/clpt.2013.186